2011
DOI: 10.1111/j.1476-5381.2011.01397.x
|View full text |Cite
|
Sign up to set email alerts
|

The endocannabinoid system as a key mediator during liver diseases: new insights and therapeutic openings

Abstract: Chronic liver diseases represent a major health problem due to cirrhosis and its complications. During the last decade, endocannabinoids and their receptors have emerged as major regulators of several pathophysiological aspects associated with chronic liver disease progression. Hence, hepatic cannabinoid receptor 2 (CB2) receptors display beneficial effects on alcoholic fatty liver, hepatic inflammation, liver injury, regeneration and fibrosis. Cannabinoid receptor 1 (CB1) receptors have been implicated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
109
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 70 publications
0
109
0
5
Order By: Relevance
“…CB1 stimulation of mouse and rat liver regeneration was reported (595,686), although CB1 may also promote hepatocellular carcinoma initiation and progression (596). Indeed, the ECS has emerged as either one of the causes or a negative modulator of most pathological aspects associated with chronic liver disease progression (525). Liver injury is associated with increased endocannabinoid tone, with AEA being produced by hepatocytes, Kupffer cells, and endothelial cells and 2-AG by hepatic stellate cells and hepatocytes (49, 525).…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…CB1 stimulation of mouse and rat liver regeneration was reported (595,686), although CB1 may also promote hepatocellular carcinoma initiation and progression (596). Indeed, the ECS has emerged as either one of the causes or a negative modulator of most pathological aspects associated with chronic liver disease progression (525). Liver injury is associated with increased endocannabinoid tone, with AEA being produced by hepatocytes, Kupffer cells, and endothelial cells and 2-AG by hepatic stellate cells and hepatocytes (49, 525).…”
Section: Livermentioning
confidence: 99%
“…Consequently, the genetic or pharmacological blockade of this pathway protects mice from liver injury also via non-cannabinoid receptor-mediated mechanisms (114). In liver injury, CB2 may become upregulated in Kupffer cells and hepatic myofibroblasts, and CB1 in hepatocytes, hepatic myofibroblasts, and endothelial cells (525).…”
Section: Livermentioning
confidence: 99%
“…One other adjunctive strategy for a cannabinoid receptor agonist may be to administer it together with a CB 1 receptor antagonist/inverse agonist. Thus, for example, it has been found that -an ultra-low dose of SR141716A can prolong R-(þ)-WIN55212-induced antinociception in a rat model of acute pain [113]; -an ultra-low dose of AM251 can enhance the ability of the CB 1 -selective agonist, arachidonyl-2 0 -chloroethylamide, to protect mice from pentylenetetrazole-induced seizures [114]; and -administration of a selective CB 1 receptor antagonist/inverse agonist together with a CB 2 -selective agonist may be particularly effective for the treatment of hepatic ischaemia/reperfusion injury caused by liver transplantation [115] and of disorders, such as Parkinson's disease [116], systemic sclerosis [117], chronic liver diseases, including alcohol-induced liver injury [56] and stroke [118], and perhaps also for the management of cocaine dependence [45,119].…”
Section: Potential Adjunctive Strategies For Cannabinoid Receptor Actmentioning
confidence: 99%
“…Sin embargo, el daño hepático en distintos grados está asociado a un aumento de la expresión de RCB 1 en hepatocitos, miofibroblastos y células endoteliales y de RCB 2 en células de Kupffer y miofibroblastos 1 . Adicionalmente, en respuesta a daño hepático agudo o crónico hay un aumento de la concentración de 2-AG en hepatocitos y en células estrelladas, y de ADA en hepatocitos, células endoteliales y de Kupffer 11,13,14 . Estos antecedentes indican la existencia de un mayor tono endocanabinoide hepá-tico en condiciones fisiopatológicas, tales como la esteatosis alcohólica y no alcohólica.…”
Section: Sec En Hígadounclassified